DHA 유도체를 이용한 항염, 항노화, 피부장벽 강화용 화장품 원료의 개발 - 이미영; Miyoung Lee; 이길용; Gil-yong Lee; 서진영; Jinyoung Suh; 이경민; Kyung Min Lee; 이우정; Woojung Lee; 조희원; Hee Won Cho; et al. (大韓化粧品學會誌, 2021)
피부 염증은 흉터, 노화 뿐만 아니라 아토피와 같은 질환으로 발전할 수 있어 이를 조절하는 것이 매우 중요하다. 본 연구에서는 최근 인체에서 염증을 조절하는 것으로 알려진 specialized pro-resolving mediators (SPMs)의 in vitro 합성과 화장품 적용 가능성을 확인하였다. 대두의 lipoxygenase를 이용하여 mono 또는 di-hydroxy docosahexaenoic acid가 혼합된 시료 S-SPMs를 제작하였고 효능 평가에 이용하였다. 먼저, UVB로 염증을 유도한 세포에서 TNF-α와 IL-6의 발현이 S-SPMs에 의해 감소하고, 미세먼지에 의해 유도된 nitric oxide (NO)의 생성 역시 감소하는 것을 확인하여 S-SPMs의 항염 효능을 확인하였다. 또한, S-SPMs을 처리한 조건에서 malondialdehyde (MDA) 생성이 감소하여 지질 과산화 억제능이 있음을 확인하였고 S-SPMs에 의한 matrix metalloproteinase-1 (MMP-1)의 발현 감소, procollagen type I의 함량 증가를 통해 collagen 분해를 억제하고 반대로 합성은 촉진함을 확인하였다. 끝으로 filaggrin과 loricrin의 발현이 S-SPMs에 의해 증가한 것을 확인하여 피부 장벽 강화 효능을 확인하였다. 위 결과를 토대로 S-SPMs은 피부의 염증 억제와 함께 손상회복, 주름개선 및 장벽 강화를 위한 소재로 활용 가능함을 확인하였다. It is very important to control the inflammation of the skin because it can develop into diseases such as atopy as well as scarring and aging. In this work, we recently identified the in vitro synthesis of specialized pro-resolving mediators (SPMs) known to control inflammation in the human body and the applicability of cosmetics. Using recombinant protein of lipoxygenase from Glycine max, we succeeded to prepare mixtures of mono- or di-hydroxy DHA named as S-SPMs and used them for in vitro efficacy test. To investigate anti-inflammatory effect of S-SPMs, mRNA level of TNF-α and IL-6 were analyzed. Under UVB exposed condition, expression of both were decreased by S-SPMs treatment. And we observed reduced production of nitric oxide (NO) by S-SPMs application under the condition with diesel particulate matter (DPM). At the same experimental condition, malondialdehyde (MDA) production was decreased by S-SPMs, indicating the inhibitory effect of S-SPMs in lipid peroxidation. In addition, S-SPMs treatment resulted in reduction of matrix metalloproteinases-1 (MMP-1) expression and elevation of procollagen type I synthesis. Together with this, mRNA level of filaggrin and loricrin were increased by S-SPMs, indicating enhancement of skin barrier function. These results demonstrate that S-SPMs is a good candidate to develop as a cosmetic ingredient for anti-inflammation, anti-wrinkle, and improvement of skin barrier function.